The Algebraic Multiplicity of the Spectral Radius of a Uniform Hypertree - Chen, Lixiang; Bu, Changjiang (The Electronic Journal of Combinatorics, 2024)
It is well-known that the spectral radius of a connected uniform hypergraph is an eigenvalue of the hypergraph. However, its algebraic multiplicity remains unknown. In this paper, we use the Poisson Formula and the matching polynomials to give the algebraic multiplicity of the spectral radius of a uniform hypertree.